Perlindungan Hukum Atas Kerugian Nasabah yang Disebabkan Bobolnya Mobile Banking Menurut Undang-Undang Nomor 10 Tahun 1998 Tentang Perbankan - Rahmawati, Defi; Tien F, Mas Anienda (Fakultas Syariah INSURI Ponorogo, 2023)
Legal protection is an effort to protect the government with a number of existing regulations. The mobile banking breach phenomenon is an incident of cyber attack on a mobile banking application that results in illegal access to a user's account and causes significant losses, such as financial losses and one's personal data. This research aims to examine legal protection for customer losses caused by the breakdown of Mobile Banking according to Law Number 10 of 1998 concerning Banking. This type of research is normative juridical with data collection methods using literature/documents. Methods of data analysis using descriptive analytical method. The data used is secondary data. This research shows that legal protection for customer losses caused by the breakdown of Mobile Banking can be pursued by legal means to obtain customer rights by means of customer complaints, settlement through LAPSPI, adjudication, arbitration, civil lawsuits.